Ekspresi CD3 dan CD26 pada Limfosit T sebagai Biomarker Potensial Penyakit Systemic Lupus Erythematosus - Suselo, Yuliana Heri; Balgis, Balgis; Indarto, Dono (Majalah Kedokteran Bandung, 2016)
Systemic lupus erythematosus (SLE) merupakan penyakit autoimun yang sering dijumpai pada wanita. Penyakit ini ditandai oleh hiperautoreaktivitas limfosit T dan B. Di dalam sistem imun, CD3 dibantu CD26 sebagai molekul kostimulator berkaitan erat dengan aktivasi dan migrasi limfosit T. Pada penyakit SLE, ekspresi CD3 dan CD26 serta aktivitas enzim CD26 belum diketahui. Tujuan penelitian ini adalah mengetahui ekspresi CD3 dan CD26 dalam darah serta kultur limfosit T pasien SLE. Rancangan penelitian ini bersifat eksperimen laboratorium dengan pendekatan studi retrospektif. Penelitian dilakukan di Laboratorium Biomedik, Fakultas Kedokteran Universitas Sebelas Maret Surakarta selama lima bulan (Mei–September 2012). Diagnosis SLE ditentukan menurut kriteria dari American College of Rheumatology (ACR). Darah vena diambil dari tiga pasien SLE dan dua orang sehat. Satu µg/mL phytohaemmaglutinin (PHA) digunakan untuk stimulasi kultur limfosit T. Ekspresi CD3 dan CD26 ditentukan dengan flows sytometry. Substrat H-Gly-Pro pNA digunakan untuk menguji aktivitas enzim CD26. Data yang terkumpul dianalisis dengan uji t. Ekspresi CD3 dan CD26 menurun dalam darah dan kultur limfosit T pada pasien SLE dibanding dengan kontrol, sedangkan aktivitas enzim CD26 pada kultur limfosit T pasien SLE lebih tinggi daripada kontrol (0.042 vs 0.030 U/mL), tetapi perbedaan tersebut tidak bermakna secara statistik (p>0.05). Simpulan, terdapat penurunan ekspresi CD3 dan CD26 baik disirkulasi darah maupun di kultur limfosit T subtipe CD4+. CD3 dan CD26 berpotensi sebagai biomarker penting untuk SLE. Namun, riset lanjutan masih perlu dilakukan untuk menjelaskan peran keduanya dalam patogenesis penyakit SLE. [MKB. 2016;48(3):140–7]Kata kunci: CD3, CD26, systemic lupus erythematosus (SLE)CD3 and CD26 Expression on T Lymphocytes as a Potential Biomarker of Systemic Lupus ErithematosusSystemic lupus erythematosus (SLE) is an autoimmune disease that is frequently found in women and characterized by hyperautoreactivity of T and B cells. In the immune system, expressions of CD 3 and CD26 (as co-stimulatory molecule) are related to T cells activation and migration. Co-expression of CD3 and CD26 in SLE patients has not been determined. The aim of this study was to investigate the co-expression of CD3 and CD26 in blood and T cell culture of SLE patients. This was an analytical descriptive study with a retrospective approach. This study was performed at the Biomedical laboratory, Faculty of Medicine, Sebelas Maret University, for five months (May–September 2012). SLE diagnosis was determined by using the criteria from the American College of Rheumatology (ACR). Vein blood was collected from three female patients with SLE and two healthy female controls. T cells isolated from the blood were cultured and stimulated with 1 µg/mL phytohaemmaglutinin (PHA). Flow cytometry was used to determine the coexpression of CD3 and CD26. CD26 enzyme activities in T cell culture were spectrophotometrically measured using H-Gly-Pro pNA substrate. Collected data were then analyzed using Student’s t test. Decreased coexpression of CD3 and CD26 was lower in blood samples and T cell cultures of SLE female patients than in control. Meanwhile, CD26 enzyme activities in SLE T cell cultures were higher than control (0.042 vs 0.030 U/mL) but no statistical difference was found (p>0.05). In conclusion, there is a decreased coexpression of CD3 and CD26 in blood circulation and T cell cultures subtype CD4+. CD3 and CD26 in SLE patients could be a prospective biomarker. Further research is required to unravel the roles of CD3 and CD26 in SLE pathogenesis. [MKB. 2016;48(3):140–7]Key words: CD3, CD26, systemic lupus erythematosus (SLE)